Pengaruh Rancangan Kegiatan Ekstrakurikuler Dalam Meningkatkan Minat Belajar Siswa di Sekolah Dasar - Hilda Fahira; Ilmi Annisa Khairani; Zulfa Ishmah Rahadatul Aisy (PT. ALHAFI BERKAH INDONESIA, 2023)
Extracurricular activities are activities that are carried out outside of the main lesson hours at school. These activities can be diverse, such as clubs, organizations, sports, arts, and others. The aim is to supplement students' education with additional experiences and skills outside the academic curriculum. Extracurricular activities give students the opportunity to explore interests and talents that are not always covered in the regular curriculum. This can trigger greater interest in learning as students feel engaged and enthusiastic in activities they enjoy. It is important to design activities so that teachers can know the progress and activities that have been carried out. The purpose of this study is to determine the importance of the influence of activity design on extracurricular activities to increase students' interest in learning in elementary schools. The activity design provides clear guidance and objectives. It helps in directing action and avoids confusion or doubt about what steps to take.